2021
DOI: 10.1016/j.medcli.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Variables del confinamiento por COVID-19 predictoras de sintomatología ansiosa y depresiva en mujeres embarazadas

Abstract: Antecedentes y objetivos La aparición de una enfermedad altamente contagiosa obligó a confinar a la población en casi todo el mundo, ocasionando el aumento de problemática psicológica, siendo las mujeres embarazadas un grupo especialmente vulnerable a sufrir consecuencias negativas. El objetivo de esta investigación fue comprobar qué variables de confinamiento o estrés psicológico están relacionadas con el aumento de la sintomatología ansiosa y depresiva en mujeres embarazadas, como consecuencia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…To finish, the finding, in this study, that pregnant women's psychological health worsened during the COVID-19 pandemic reveals the need to encourage the use of psychological tools that have proven to be effective in reducing both stress and psychological discomfort in this population ( Romero-Gonzalez et al, 2020 ). One such tool would be cognitive behavioural therapy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To finish, the finding, in this study, that pregnant women's psychological health worsened during the COVID-19 pandemic reveals the need to encourage the use of psychological tools that have proven to be effective in reducing both stress and psychological discomfort in this population ( Romero-Gonzalez et al, 2020 ). One such tool would be cognitive behavioural therapy.…”
Section: Discussionmentioning
confidence: 93%
“…A study carried out in Spain by Romero-Gonzalez et al 2020 , has shown that perceived stress, specific pregnancy stress, as well as insomnia are predictive variables in most anxiety and depressive symptoms related to COVID-19 in pregnant women. However, this study did not have a control group to compare the psychopathology of pregnant women prior to the pandemic and after the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety among pregnant women may be affected by the COVID-19 pandemic due to their perceived stress (Preis et al, 2020a ; Romero-Gonzalez et al, 2021 ). Perceived stress is experiencing distress while responding to stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the relation between perceived stress and anxiety among pregnant women during the COVID-19 pandemic overwhelmingly took a variable-centered approach that overlooked individual differences (e.g., Preis et al, 2020a ; Romero-Gonzalez et al, 2021 ). Although some studies have found that both HEL and SEL can predict psychological problems (e.g., depression; Hewitt et al, 1992 ), others have found that HEL but not SEL is related to psychological problems (Martin et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…Frente a la epidemia de la COVID-19, se necesita una inmediata atención; de modo que la aparición de esta pandemia obligó a confinar a la población mundial (3) . Se han utilizado diversas medidas para reducir el impacto de la COVID-19, como el aislamiento físico o el cierre temporal de fronteras territoriales, instituciones académicas y lugares públicos (4) , toda persona debe tomar las precauciones necesarias, con un compromiso consciente y responsable, tanto a nivel individual como colectivo, para controlar y adaptarse a la nueva normalidad; lo que exige un compromiso consciente y responsable de todos, ante la pandemia (5) .…”
Section: Introductionunclassified